Comparative effectiveness of non-pharmacological therapies for postoperative cognitive dysfunction: Protocol for a systematic review and network meta-analysis. - Kexin Wu; Qiongnan Bao; Jun Huang; Shanshan Sun; Yaqin Li; Xinyue Zhang; Manze Xia; Zhenghong Chen; Jin Yao; Wanqi Zhong; Zihan Yin; Fanrong Liang (PLoS ONE)
Introduction Postoperative cognitive dysfunction (POCD) is a common complication following surgery. Electroacupuncture (EA), manual acupuncture (MA), transcutaneous electrical acupoint stimulation (TEAS), and cognitive training (CT) can effectively maintain or improve the postoperative cognitive function of patients. However, it remains unclear which therapy is the most effective. Therefore, this network meta-analysis aims to compare and rank the efficacy of these non-pharmacological therapies for POCD to identify the optimal therapy. Methods and analysis A systematic search will be conducted across seven databases (PubMed, Cochrane Library, EMBASE, Web of Science, CINAHL, AMED, and PsycINFO) for articles published between January 2000 and November 2023. Two reviewers will independently conduct study selection and data extraction. The primary outcome will be the changes in the overall cognitive function before and after the intervention. The secondary outcome will be the incidence of POCD. The risk of bias will be assessed using the revised Risk of Bias Assessment Tool. Pairwise and Bayesian network meta-analyses will be performed using RevMan, STATA, and Aggregate Data Drug Information System statistical software. Additionally, the quality of evidence will be assessed using the Grading of Recommendations Assessment, Development, and Evaluation guidelines. Ethics and dissemination: The results will be disseminated to peer-reviewed journals or conferences. Trial registration PROSPERO registration number: CRD42023454028.